Analisis Penerapan ISAK 335 dalam Pelaporan Keuangan Organisasi Nirlaba: Studi Kasus Pada Tiga Masjid di Kabupaten Tanah Datar, Sumatera Barat - Claudea Amanda; Putri Putri; Riza Yulia Putri; Rena Karmila; Misbah Yusri; Sri Adella Fitri (Jurnal Mutiara Ilmu Akuntansi, 2026)
Religious institutions such as mosques are part of non-profit public sector entities that manage public funds and therefore require accountable and transparent financial reporting standards. ISAK 335 is the applicable standard governing the presentation of financial statements for non-profit-oriented entities in Indonesia. This study aims to analyze the conformity of financial management practices in three mosques in Tanah Datar Regency, West Sumatra, namely Baiturrahman Mosque Sungayang, Nurul Huda Mosque Simpuruik, and Al-Amin Mosque Dobok Batusangkar, with the provisions of ISAK 335. The approach used in this research is a descriptive qualitative approach with data collection conducted through interviews and observations. The results of the study indicate that the three mosques have not implemented ISAK 335 in the preparation of their financial statements. Financial management practices are still limited to recording cash receipts and cash disbursements without the classification of net assets, statements of financial position, statements of activities, or notes to financial statements standardized in accordance with ISAK 335. The main inhibiting factors include limited human resources in the field of accounting, lack of standard dissemination, and minimal regulatory pressure. This study recommends the need for continuous training, technical assistance, and stronger regulations for mosque financial managers so that mosque financial statements can be prepared and presented in accordance with the applicable standards for non-profit organizations, namely ISAK 335.